(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article notes that according to the previously valid marriage and family legislation of the Kyrgyz Republic, the property relations of the spouses were regulated only by law, other agreements of the spouses were not contained in the legislation. The Institute of Contractual Regime of Marital Property is a new institute of family law in the Kyrgyz Republic. It gives the spouses the right to independently determine the content of their property relations (rights and obligations) in the marriage contract. The concept of a «prenuptial agreement» has appeared in Kyrgyz legislation relatively recently. On August 30, 2003, the Family Code of the Kyrgyz Republic entered into force. Chapter 9 «contractual regime of marital property», which is part of it, gives an idea of the marriage contract and defines the conditions for its conclusion and termination, as well as gives a list of legal relations regulated by this agreement.